Argue with me : argument as a path to developing students' thinking and writing - Kuhn, Deanna, 1944- (Eye on Education book, 2016)
It is essential that middle- and high-school students develop argument skills. This rich resource provides a clear, step-by-step approach that achieves this goal. The method is rooted in peer dialog and makes use of readily available technology. The authors document impressive gains in students'skills in producing and interpreting both dialogic and written arguments. The method can be used in English or content-area classes, or even be implemented as a stand-alone class or as part of a debate program. This curriculum helps students become critical thinkers prepared for the demands of college, careers, and citizenship. Book Features: Background on why students should develop argument skills and what these skills consist of The nuts and bolts of how to implement the curriculum in your own classroom Alignments to the Common Core State Standards and Next Generation Science Standards Accessible video material showing both teacher's instructions and students'activities Samples of students'written work Assessment tools that you can use or modify to fit your own needs An appendix with additional guides, examples, suggested topics, and classroom-ready reproducibles. New to the second edition is a chapter on how you can incorporate this approach into an existing curriculum if you are unable to implement the full program.The techniques are designed to be flexible and adaptable, and work with students of all ability levels - especially with those who are less motivated and engaged in school.